Fair chances and hard work? Families making sense of inequality and opportunity in 21st‐century Britain. (21st February 2018) - Snee, Helene; Devine, Fiona
Abstract: In British social mobility discourse, the rhetoric of fair access can obscure wider issues of social justice. While socio‐economic inequalities continue to shape young people's lives, sociological work on class dis‐identification suggests social class is less obviously meaningful as a source of individual and collective identity. This paper considers subjective understandings of the post‐16 education and employment landscape in this context, drawing on qualitative research exploring the aspirations of young men and women as they completed compulsory education in north‐west England, and the hopes their parents had for their future. It shows how unequal access to resources shaped the older generation's expectations for their children, although this was rarely articulated using the explicit language of class. Their children recognized they faced a difficult job market but embraced the idea that success was possible through hard work. Both generations drew moral boundaries and made judgments based on implicit classed discourses about undeserving others, while at the same time disavowing class identities. There was a more explicit recognition of gender inequality among the parents framed with reference to hopes for greater freedom for their daughters. Opportunities and inequalities were thus understood in complex and sometimes contradictory ways.